1979
DOI: 10.1079/bjn19790072
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pregnancy and lactation on the activities of trypsin and α-chymotrypsin in the rat pancreas

Abstract: I . The food intake, pancreas weight and trypsin (EC 3 . 4 . 2 1 . 4 ) and a-chymotrypsin (EC 3 . 4 . 2 1 . I ) activities in the pancreas were measured in rats during pregnancy and lactation and after the young were weaned.2. All the quantities measured increased significantly during lactation and had returned to their original values by 4 weeks after weaning. Food intake and pancreas weight were highest after the second week of lactation. Total trypsin and a-chymotrypsin activity, and the activity per g tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…These experiments show that some metabolic enzymes, like the digestive enzymes investigated in previous work (Rolls, 1975;Rolls et al, 1979), increase during pregnancy and lactation in the rat and that, at least in some instances, these increases are in excess of those expected simply from enlargement of the gut. These changes in total activity can be contrasted with the findings of Burdett, Green & Reek (1978) who studied a range of metabolic enzymes in different regions of the gut histochemically and reported some increases in activity during pregnancy but, in general, no further increases in lactation.…”
Section: Analysis and Measurement Ofenzyme Activitiesmentioning
confidence: 78%
See 3 more Smart Citations
“…These experiments show that some metabolic enzymes, like the digestive enzymes investigated in previous work (Rolls, 1975;Rolls et al, 1979), increase during pregnancy and lactation in the rat and that, at least in some instances, these increases are in excess of those expected simply from enlargement of the gut. These changes in total activity can be contrasted with the findings of Burdett, Green & Reek (1978) who studied a range of metabolic enzymes in different regions of the gut histochemically and reported some increases in activity during pregnancy but, in general, no further increases in lactation.…”
Section: Analysis and Measurement Ofenzyme Activitiesmentioning
confidence: 78%
“…Some of the changes produced by pregnancy and lactation in various extra-reproductive organs have been reviewed by Fell (1977) and Rolls, Henschel & Palmer (1979). In particular, we have shown that the activities of some enzymes responsible for protein digestion are increased in the small intestine (Rolls, 1975) and in the pancreas (Rolls et al, 1979), slightly in pregnancy and markedly during lactation.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the late stage of pregnancy and during the lactation period, hypertrophy and hyperplasia of the gastrointestinal organs occur, such as an increase in the weight of the stomach, increase in the intestinal mucosal surface area, hyperplasia of the small intestinal epithelium and increase in crypt length and villus height (Crean & Rumsey, 1971 ;Cripps & Williams, 1975;Rolls, 1975;Jolicoeur et al 1980;Remesar et al 1981). These changes are induced by increases in the plasma level of gastrointestinal hormones such as gastrin, secretin and cholecystokinin (CCK), which have been shown to have significant trophic effects on the gastrointestinal organs (Rolls et al 1979). Gastrin and CCK stimulate not only the secretion of exocrine pancreatic enzymes but also their synthesis in the acinar cells (Mainz et al 1973;Barrowman & Mayston, 1974).…”
mentioning
confidence: 99%